Analisis Posisi Optimal Pengangkatan Balok U-Shell Dengan Menggunakan Crane - Ahmad Hamidi (Universitas Trisakti, 2019)
Riau University Education Hospital was built to support lectures and as a tool in research in the field of health. Teaching Hospital was built using U-Shell precast blocks with consideration of time and cost efficiency in project implementation. U-Shell beams are made at the project site and the method of lifting precast beams is generally recommended from the factory. While the U-Shell beam is made at the project site, it is necessary to calculate the lifting distance so that the beam when moved does not occur due tomoment damage. U-Shell beam lifting calculation is done with several alternatives, namely the position of 1 /3L, 1 / 4L and pedestal xL. The result of the moment calculation shows the moment value for each alternative, namely in the beam with dimensions of 350 mm x 800 mm position 1 / 3L M1 of-1242 Kgm and M2 of-931.5 Kgm, at position 1 / 4L M1 of-698.63 Kgm and M2 of 0, at position 1 / 5L M1 of-478.97 Kgm and M2 of 480.64 Kgm. As for the beam with dimensions of 300 mm x 700 mm position 1 / 3L M1 of -460.8 Kgm and M2 of -345.6 Kgm, at position 1 / 4L M1 of -256.2 Kgm and M2 of 0, at position 1 / 5L M1 of - 177.7 kg and M2 of 178.32 kg. From the three alternatives we get an effective lifting position, which is 1 / 5L.